"Second guessing yourself all the time about what they really mean…": Cognitive differences between autistic and non‐autistic adults in understanding implied meaning. Issue 1 (20th July 2020) - Wilson, Alexander C.; Bishop, Dorothy V. M.
Abstract : Abstract: This study investigated cognitive differences between autistic and non‐autistic people in understanding implied meaning in conversation using a novel computerized test, the Implicature Comprehension Test. Controlling for core language ability, autistic participants ( N = 66) were over twice as likely to endorse a non‐normative interpretation of an implied meaning and over five times as likely to select "do not know" when asked about the presence of an implied meaning, compared to non‐autistic participants ( N = 118). A further experiment suggested that the selection of "do not know" reflected a cognitive preference for certainty and explicit communication, and that the normative inference could often be made when the test format was more constrained. Our research supports the hypothesis that autistic individuals can find it challenging to process language in its pragmatic context, and that cognitive preferences play a role in this. Lay summary: We investigated differences between autistic and non‐autistic people in understanding implied meanings in conversation. We found that autistic people were more likely to select a different interpretation of implied meanings compared to other people, and also much more likely to avoid processing implied meanings when the task allowed this. Our research supports the view that autistic people can find it challenging to process indirect meanings, and that they tend to prefer explicit forms of communication.